Interferon Alpha-Inducible Protein 27 Expression Is Linked to Disease Severity in Chronic Infection of Both HIV-1 and HIV-2 - Palm, Angelica A.; Veerla, Srinivas; Lindman, Jacob; Isberg, Per-Erik; Johansson, Emil; Biague, Antonio; Månsson, Fredrik; Norrgren, Hans; Esbjörnsson, Joakim; Medstrand, Patrik; Jansson, Marianne (Frontiers in Virology, 2022)
Disease progression is slower in HIV-2, as compared with HIV-1 infection, in accordance with low or undetectable plasma viremia at viral setpoint. However, it is unclear why most HIV-2 infected individuals are still at risk of developing AIDS. To explore if specific host responses are linked to HIV disease severity, we have compared blood gene expression profiles between HIV seronegative and HIV-1, HIV-2 or dually HIV-1/HIV-2 infected individuals. In this study the gene encoding Interferon alpha-inducible protein 27 (IFI27) was found to be the most differentially expressed. Detailed expression analysis revealed significantly higher IFI27 expression in HIV infected individuals compared with seronegative individuals, irrespectively of HIV type. Moreover, IFI27 expression was higher in HIV-1 than in HIV-2 infected individuals. Multiple linear regression analysis, adjusting for age and sex, showed also that plasma viral load was the strongest predictor of IFI27 expression, followed by CD4% and HIV type. In line with this, IFI27 expression was found to be higher in HIV-2 viremic, compared with HIV-2 aviremic individuals. Still, HIV-2 aviremic individuals displayed elevated IFI27 expression compared with seronegative individuals. Furthermore, in HIV-2 infected individuals, IFI27 expression was also correlated with plasma markers previously linked to inflammation and disease progression in HIV infection. Taken together, our findings suggest that sustained elevation of type I interferon signaling, here reflected by elevated IFI27 expression in the chronic infection phase, is a key pathogenic feature of both HIV-1 and HIV-2.